Successful Treatment of Methampyrone-Induced Toxic Epidermal Necrolysis with Therapeutic Plasma Exchange. (18th July 2018) - Santosa; Rumbiana, A.; Wahab, Z.; Kurniawan, S. P.; Naibaho, R. M.; Yogyartono, P.
Abstract : The toxic epidermal necrolysis (TEN) is a severe cutaneous adverse reaction frequently caused by drug exposure. A 58-year-old male was admitted to the hospital after administration of methampyrone. He developed sloughing of the total epidermis which rapidly extended over the trunk and limbs. The presumptive diagnosis was drug-induced TEN. Despite the treatment with pulsed glucocorticoid and cyclosporine, the skin lesions extended over the entire body. Strikingly, the progression of blistering was stopped by therapeutic plasma exchange (TPE). TPE was discontinued after the signs of skin inflammation had been overcome. He recovered in 8 days of hospitalization. We present here a case of a methampyrone-induced TEN which was successfully treated with TPE.